SWOT ANALYSIS FOR DEVELOPING THE SIROMBU BEACH TOURISM OBJECT, SIROMBU DISTRICT, WEST NIAS DISTRICT - Feby Milanie; Selviana Ginting; Arwadi Asmar Jaya Gulo; Hati'aro Lahagu; Analisis Gulo (Journal of International Islamic Law, Human Right and Public Policy, 2024)
This research aims to analyze opportunities, weaknesses and threats in developing the Pantai Indah Sirombu tourist attraction, Sirombu District, West Nias Regency. So that strategies can be formulated to develop tourist attractions by minimizing weaknesses and threats, maximizing the utilization of opportunities and strengths. Data collected through literature study, observation and interviews with community leaders, the Tourism Office, the community around the tourist attraction and visitors to Pantai Indah Sirombu. The data was analyzed descriptively and then to determine the development strategy for the Pantai Indah Sirombu tourist attraction, a SWOT analysis was carried out. Based on the research results, it can be concluded that the strategy for developing the Pantai Indah Sirombu tourist attraction includes building infrastructure such as road access, transportation equipment and accommodation facilities, creating tourist attractions and promoting tourist attractions, developing tourism products, and involving the community in tourism management.